On the Existence of Ionospheric Feedback Instability in the Earth's Magnetosphere‐Ionosphere System. Issue 11 (20th November 2018) - Streltsov, Anatoly V.; Mishin, Evgeny V.
Abstract: The ionospheric feedback instability (IFI) has been considered one of the main generation mechanisms for large‐amplitude ultralow frequency waves and small‐scale field‐aligned currents in the auroral and subauroral regions for more than 40 years. Sydorenko and Rankin (2017, https://doi.org/10.1002/2017GL073415 ) have recently challenged the very existence of the IFI for any realistic geophysical conditions in the Earth's ionosphere‐magnetosphere system. Because this conclusion contradicts numerous theoretical, numerical, and experimental works successfully used IFI to explain and predict results from observations for more than four decades, it deserves special attention. We show that this conclusion is mainly based on the specific ionospheric density profile and boundary conditions used in two runs of simulations presented in Sydorenko and Rankin (2017), and the generalization of this result is not justified. The effect of the collisions between ionospheric ions and neutrals on the development of the instability has been well studied since 1981, and these studies demonstrate that it does not prevent the development of the instability. Furthermore, excellent agreement of the theoretical and numerical results with observations verify without doubt the IFI existence and significance in the Earth's magnetosphere‐ionosphere system. Key Points: We review the conclusion from Sydorenko and Rankin (2017) on the existence of the ionospheric feedback instability in Earth's ionosphere We show that this conclusion contradicts to numerous theoretical and observational studies of this phenomena We present arguments supporting the existence of IFI in the Earth's magnetosphere‐ionosphere system